Extraction of the anisotropic dielectric properties of materials from polarization-resolved terahertz time-domain spectra - Castro-Camus, E; Johnston, M (2009)
The anisotropic complex dielectric properties of materials in the terahertz band is a topic that has attracted considerable attention recently in the fields of physics, chemistry and biochemistry. The mathematical formalism for analysing polarization-resolved terahertz time-domain data is presented, and particular cases including birefringence, optical activity and circular dichroism are discussed. © 2009 IOP Publishing Ltd.